Protecting rivers by integrating supply-wastewater infrastructure planning and coordinating operational decisions. (26th November 2020) - Dobson, Barnaby; Mijic, Ana
Abstract: Placing water quality in rivers at the centre of water infrastructure planning and management is an important objective. In response there has been a range of 'whole system' analyses. Few studies, however, consider both abstraction (water removed from rivers) and discharge (water returned) to inform the future planning of water systems. In this work we present a systems approach to analysing future water planning options where system development prioritises the water quality of the receiving river. We provide a theoretical demonstration by integrating water supply and wastewater infrastructure, and downstream river water quality, on an open-source, stylised, systems model for London, UK, at a citywide scale. We show that models which consider either supply or wastewater separately will underestimate impacts of effluent on the water quality, in some cases by amounts that would require £1 billion worth of infrastructure equivalent to mitigate. We highlight the utility of the systems approach in evaluating integrated water infrastructure planning using both socio-economic and environmental indicators. Through this approach we find unintended impacts from planning options on downstream river quality; including benefits from water demand management and rainwater harvesting, and costs from wastewater reuse. Finally, we present a novel management planning option between supply and wastewater, which we refer to as Abstraction-Effluent Dilution (AED), that is, to reduce river abstractions during high precipitation events to dilute untreated sewer spills. The AED option is found to provide up to £200 million worth of equivalent infrastructure in river quality improvements and has minimal impact on the reliability of water supply while requiring only a change in operational decision making. This proof-of-concept study highlights that seeing our water systems differently with this holistic approach could fundamentally change the way we think about future water infrastructure planning so that it works both for people and the environment.